Instrumentation for Verification of Shunt Active Power Filter Algorithms - Baros, Jan; Bilik, Petr; Jaros, Rene; Danys, Lukas; Strossa, Jan; Hlavaty, Lukas; Martinek, Radek (Sensors (Basel, Switzerland), 2023)
This article presents a comprehensive system for testing and verifying shunt active power filter control methods. The aim of this experimental platform is to provide tools to a user to objectively compare the individual control methods. The functionality of the system was verified on a hardware platform using least mean squares and recursive least squares algorithms. In the experiments, an average relative suppression of the total harmonic distortion of 22% was achieved. This article describes the principle of the shunt active power filter, the used experimental platform of the controlled current injection source, its control system based on virtual instrumentation and control software and ends with experimental verification. The discussion of the paper outlines the extension of the experimental platform with the cRIO RTOS control system to reduce the latency of reference current generation and further planned research including motivation.